Synthesis of 2-(Arylselanyl)benzo[b]chalcogenophenes via Intramolecular Cyclization of Vinyl Selenides - Stach, Guilherme; Peglow, Thiago J.; Roehrs, Juliano A.; Penteado, Filipe; Barcellos, Thiago; Jacob, Raquel G.; Lenardão, Eder J.; Perin, Gelson (Synthesis, 2019)
An efficient protocol to access 2-arylselanylbenzo[b]chalcogenophene derivatives through the Cu(I)-catalyzed annulation of vinyl selenides is described. The key vinyl selenides were easily prepared from properly functionalized 1,1-dibromostyrenes and the method allowed the synthesis of 2-arylselanylfurans, -thiophenes, and -selenophenes in moderate to excellent yields.
Keywords: 2-arylselanylbenzo[b]chalcogenophenes; copper catalysis; annulation